A Community Health Worker-Led Positive Psychology Intervention for African American Older Adults With Chronic Pain. (8th April 2022) - Janevic, Mary; Robinson-Lane, Sheria G; Courser, Rebecca; Brines, Elizabeth; Hassett, Afton L
Abstract: Background and Objectives: Experiencing structural racism over the life course contributes to disproportionate pain-related disability among African American older adults. Positive STEPS, delivered by community health workers, is a culturally congruent chronic pain self-management intervention that incorporates positive psychology principles and gives attention to social determinants of pain and pain management. Research Design and Methods: We conducted a randomized pilot trial among older adults with chronic musculoskeletal pain in an underserved, primarily African American community (Detroit, Michigan). The 7-week intervention included weekly telephone sessions with a community health worker; web-based videos teaching pain self-management skills; positive activities (e.g., Life Review, Gratitude Jar); and use of wearable activity trackers. Outcomes were measured at baseline and 8-week follow-up. We assessed participant retention, engagement, and satisfaction. Results: Study completers ( n = 46; 90% retention) were 93% African American, 89% female, mean 72 years, and completed 5.7 of 7 sessions. Intervention participants versus controls showed greater improvement in PROMIS Pain Interference (4.3-point T -score decrease vs. 0.4-point increase; p = .01) and the Pain Self-Efficacy Questionnaire ( p = .007). Furthermore, compared with controls, significantly more intervention participants reported "better" or "much better" global functioning (86% vs. 25%; p = .000) and pain (67% vs. 21%; p = .003) since baseline. Improvements in physical functioning, social participation, and resilience were noted, but differences were not significant. Participant feedback on the intervention was overwhelmingly positive. Discussion and Implications: A community health worker-led chronic pain self-management intervention combining positive activities with self-management skills training demonstrated the potential to enhance pain-related functioning among a vulnerable group of older adults. Clinical Trial Number: NCT04321239